Backfire Effect: Using Hegemony to Explore Our Own Positionality - Kwon, Hee Eun (TRAILS: Teaching Resources and Innovations Library for Sociology, 2022)
This in-class activity is designed to help students understand the theory of racial formation in the United States by having them identify “hegemony” in relation to their own positionality. Using the backfire effect as a medium to explain the elements of coercion and consent, this activity allows students to draw from their experiences to see why and how hegemonic ideals are accepted, normalized, and reproduced over time. By offering students the opportunity to connect the course materials to their lived experiences, this activity also enables them to share any emotional responses they might have had to the readings, class discussion, or current events pertaining to racial formation in the United States. In doing so, students also learn to recognize and develop a critique of colorblindness. Suited for both upper- and lower-division sociology courses, this activity could be utilized in any lecture/discussion about race relations or positionality; this can include courses on immigration, race, and ethnicity, as well as other general sociology courses given the omnipresence of race as a way of making up people.